Prediction of live birth in vitrified-warmed 1PN-derived blastocyst transfer: Overall quality grade, ICM, TE, and expansion degree - Wang, Tiantian; Si, Jiqiang; Wang, Bian; Yin, Mingru; Yu, Weina; Jin, Wei; Lyu, Qifeng; Long, Hui (Frontiers in Physiology, 2022)
Background: Numerous studies have reported that transfer of blastocysts derived from monopronuclear (1PN) zygotes achieved live births. However, the potential value of morphology grading for the prediction of 1PN blastocyst viability is unclear, and the blastocyst selection criterion for successful pregnancy has not been set up yet. The aim of this study is to assess the ability of the blastocyst morphology grading system based on three parameters, namely, inner cell mass (ICM), trophectoderm (TE), and expansion degree and to predict outcomes of a cycle with single 1PN blastocyst transfer. Methods: A total of 266 vitrified-warmed 1PN-derived blastocyst transfer cycles for IVF treatment at Shanghai Ninth People’s Hospital between 2007 and 2020 were included. The study was performed on single blastocyst transfers. Electronic records of patients were retrospectively analyzed. In the current study, the blastocysts were classified into three groups: “good,” 3-6AA, 3-6AB, 3-6BA; “medium,” 3-6BB, 3-6AC, 3-6CA; and “poor,” 3-6BC, 3-6CB, 3-6CC. The basal characteristics, embryo grading, and clinical outcomes were compared between the three groups. The association of morphology parameters with pregnancies and live births was analyzed. Logistic regression was adopted to set up a prediction model of live births. Results: Transfer of the good-quality blastocysts achieved significant higher pregnancies (biochemical pregnancy: 59%; clinical pregnancy: 56.4%, and live birth 48.7%) than those in the group of the medium (biochemical pregnancy: 59%; clinical pregnancy: 49.6%; live birth: 40.4%) or poor-quality (biochemical pregnancy: 38.4%; clinical pregnancy: 34.9%; live birth: 26.7%) blastocysts (p < 0.05). There was a significant association between ICM and live birth. A prediction model of live births involving ICM, TE, and expansion degree was set up. Conclusion: In 1PN transfer cycles, a higher overall blastocyst quality is shown to correlate most strongly with optimal pregnancy and live birth outcomes. The selection of high-quality blastocysts for transfer should consider the ICM score first. The prediction model of live births based on ICM, TE, and expansion degree may help predict successful pregnancy in 1PN single-blastocyst transfer cycles.